2016
DOI: 10.1002/14651858.cd012183
|View full text |Cite
|
Sign up to set email alerts
|

Biologics or tofacitinib for rheumatoid arthritis in incomplete responders to methotrexate or other traditional disease-modifying anti-rheumatic drugs: a systematic review and network meta-analysis

Abstract: Based primarily on RCTs of 6 months' to 12 months' duration, there is moderate quality evidence that the use of biologic+MTX/DMARD in people with rheumatoid arthritis who have failed to respond to MTX or other DMARDs results in clinically important improvement in function and higher ACR50 and remission rates, and increased risk of serious adverse events than the comparator (MTX/DMARD/PL; high quality evidence). Radiographic progression is slowed but its clinical relevance is uncertain. Results were inconclusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
1
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 245 publications
2
53
1
10
Order By: Relevance
“…Insufficient inhibition of structural joint damage by disease-modifying antirheumatic drugs (DMARDs) was reported despite clinical improvement,3–5 and recently two meta-analysis6 7 showed that methotrexate combined with biologics is statistically superior to methotrexate in inhibiting radiographic progression, but the estimated mean change with all treatments was less than the minimal clinically important difference.…”
mentioning
confidence: 99%
“…Insufficient inhibition of structural joint damage by disease-modifying antirheumatic drugs (DMARDs) was reported despite clinical improvement,3–5 and recently two meta-analysis6 7 showed that methotrexate combined with biologics is statistically superior to methotrexate in inhibiting radiographic progression, but the estimated mean change with all treatments was less than the minimal clinically important difference.…”
mentioning
confidence: 99%
“…One review assessed the safety and effectiveness of bDMARDs and tofacitinib in patients that had shown an inadequate response to csDMARD treatment 17 . It used data from 79 trials (32,874 participants), including three trials that assessed tofacitinib efficacy at 12 weeks.…”
Section: What Are Baricitinib and Tofacitinib?mentioning
confidence: 99%
“…It used data from 79 trials (32,874 participants), including three trials that assessed tofacitinib efficacy at 12 weeks. In patients who failed to show an adequate response to csDMARDs, the authors concluded that there was no significant difference between the improvement in ACR50 response of tofacitinib plus methotrexate/csDMARD compared with a bDMARD plus methotrexate/csDMARD (OR 1.28, 95% CI 0.61 to 2.71) 17 . Similarly, in patients taking a csDMARD/methotrexate there was no significant difference shown between the likelihood that the addition of a bDMARD would induce a larger reduction in HAQ scores than tofacitinib.…”
Section: What Are Baricitinib and Tofacitinib?mentioning
confidence: 99%
“…Such therapies have dramatically altered outcomes for a range of diseases, including rheumatoid arthritis (RA), psoriasis and Inflammatory Bowel Disease (IBD) 1 . However, even for a disorder like rheumatoid arthritis (RA) in which much progress has been made, most patients do not respond completely to currently available therapies, and there are relatively few examples of long-term remissions after cessation of therapy 2 . For other disorders, there has been even less progress, especially diseases in which fibrosis and tissue destruction are major features, such as systemic sclerosis.…”
Section: Introductionmentioning
confidence: 99%